Transforming Educators' Competencies for Human-Centered Learning in the Era of Artificial Intelligence: A Literature Review from the Perspective of Islamic Educational Values - Muhammad Burhan Ashfiya'; Zia Datul Amalia; Nadhirotul Burda; Fatimah Azzahro; Alawiyatus Sofanin; Imam Syafi’i (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
The development of Artificial Intelligence has created significant opportunities for educational transformation through more adaptive and personalized learning innovations. However, the rapid penetration of digital technology also raises the risk of educational dehumanization when learning processes become overly oriented toward automation and technological efficiency. This study aims to analyze the transformation of educators’ competencies from the perspective of human-centered learning in the era of Artificial Intelligence. The study employed a descriptive qualitative approach using a library research method by analyzing national scientific articles published between 2020 and 2026 and indexed through Google Scholar. The data were analyzed using literature analysis techniques to identify thematic patterns, research tendencies, and conceptual syntheses related to teacher competencies in the AI era. The findings indicate that educators’ competencies have shifted from conventional pedagogical competencies toward multidimensional competencies encompassing AI literacy, human-centered pedagogy, empathetic communication, reflective leadership, and technology-based collaborative learning. Human-centered learning has emerged as a dominant paradigm emphasizing empathy, social interaction, critical reflection, and meaningful learning experiences as the core of educational processes. The integration of AI has improved learning personalization, administrative efficiency, and instructional media innovation, yet it also poses the potential to weaken humanistic dimensions if not balanced with ethical and social values. This study contributes theoretically to strengthening the discourse on AI-based human-centered learning and practically serves as a foundation for developing teacher training programs, AI literacy, and humanistic educational policies in Indonesia.